Restoring commercial timber species through silvicultural patch clear-cuts and natural regeneration in Mexico’s Maya Forest: Composition and growth 11 years after three treatments - Snook, Laura K.; Capitanio, R.; Tadeo-Noble, A. (Elsevier, 2021)
The natural regeneration of 27 commercial and potentially commercial timber species was studied on experimental clearings in managed forests on three ‘ejidos’ and one private property in Quintana Roo, Mexico. Eight ½ ha clear-cuts had been created 11 years earlier using each of three different clearing treatments: slashing, felling and leaving (felled); slashing, felling and burning (burned); and machine-clearing. More than 6000 trees of 108 species were identified and measured on six 49 m2 quadrats on each of the experimental clear-cuts, and on the same number and size of quadrats in the neighboring forest. The Basal Area (BA) of different commercial timber groups differed among treatments. After machine-clearing, 47% of the BA was made up of currently commercial timber species, 39% the more valuable decorative hardwoods and 8% lesser value softwoods; on burned treatments, 40% of the BA was currently commercial timber species, 29% decorative hardwoods and 11% softwoods. On both these treatments Lysiloma latisiliquum, one of the most valuable hardwoods, accounted for more than 25% of the BA. On felled treatments, 29% of the BA was commercial timber species; 6% decorative hardwoods, 22% softwoods and 1% precious woods (Swietenia macrophylla). On controls, currently commercial species accounted for 27% of the BA, of which 21% was decorative hardwoods, 5% softwoods and 1% precious woods. The decorative hardwood species L. latisiliquum did not occur on control plots and was rare on felled plots. Depending on the treatment, palms and non-commercial species accounted for 31% to 52% of the BA, and ‘potentially commercial’ species or ‘other species of commercial interest’ accounted for 15% to 41% of the BA. On felled clearings, 30% of individuals were sprouts, as compared to 19% on burned clearings and 11% after machine-clearing. The largest trees on burned and machine-made clearings had grown approximately 1 cm in diameter year−1. Opening small clearings within the forest matrix using the same slash and burn treatments that local farmers use to open their agricultural fields, or machines like bulldozers, stimulated the natural regeneration of commercially valuable decorative hardwood species, of which 75% have been classified as shade-intolerant. These do not regenerate satisfactorily under the current regime of selective logging. The silvicultural management system for the Maya Forest must include patch clear-cuts and the conservation of seed trees and their pollinators and dispersors to sustain the commercial timber value of the forest, and its biodiversity.